Tardy ulnar nerve palsy caused by chronic radial head dislocation after Monteggia fracture: a report of two cases. Issue 5 (September 2016) - Nishimura, Masahiro; Itsubo, Toshiro; Horii, Emiko; Hayashi, Masanori; Uchiyama, Shigeharu; Kato, Hiroyuki
Abstract : Dislocation of the radial head is often encountered as a result of a pediatric Monteggia fracture. We report two rare cases of tardy ulnar nerve palsy associated with anterior radial head dislocation combined with anterior bowing of the ulna. They had cubitus valgus deformity, valgus instability, and osteoarthritis of the elbow, and had elbow injury more than 40 years back. They were diagnosed with chronic radial head dislocation long after a Bado type 1 Monteggia fracture. Anterior subcutaneous ulnar nerve transposition yielded favorable results. It is important to recognize the possibility of tardy ulnar nerve palsy caused by an improperly treated Monteggia fracture.